Anxiety and depression in patients with alpha-1 antitrypsin deficiency: current insights and impact on quality of life - Beiko T; Strange C (Dove Medical Press, 2019)
Tatsiana Beiko, Charlie StrangeDivision of Pulmonary and Critical Care Medicine, Medical University of South Carolina, Charleston, SC, USAAbstract: Chronic physical illness is associated with significant vulnerability for emotional disorders. Some studies suggest anxiety and depression are common comorbidities in individuals with alpha-1 antitrypsin deficiency (AATD). Many aspects of AATD contribute to quality of life impairment. Delays in diagnosis, high costs of disease treatment, and inherited genetic risk add to the symptom burden of lung or liver disease to alter quality of life. Whether anxiety and depression independently contribute to quality of life impairment remains unproven. In this article, we aim to review current literature examining the impact of anxiety and depression on the quality of life of AATD-affected individuals. Multifaceted approaches may best meet the needs of a heterogeneous population and are the best future strategies to minimize these emotional impacts and assure highest quality of life possible. More research studies are needed to achieve this ambitious goal and make life of AATD-affected individuals better by minimizing the effects of anxiety and depression.Keywords: anxiety, depression, alpha-1 antitrypsin deficiency